2
$\begingroup$

For the IVP, $y'+\frac{2x^2-4xy-y^2}{3x^2}=0, x>0, y(1)=y_0$

I got this, once all the calculations have been done: $$y'=\frac{y_0^2(-2x^2+4x+1)+4y_0(x^2+x+1)-2(x^2+4x-2)}{(2+y_0-x(y_0-1))^2}$$

I am confident with this calculation, and I also verified with Wolfram Alpha. Then the question asked there is exactly one value of $y_0$ such that the IVP satisfied $\lim_{x\to 0}y'(x)\neq 1$, while $\lim_ {x\to0}y'(x)=1$ for all other values of $y_0$. What is this value of $y_0$ corresponding to the different limits?

So I took the limit $$\lim_{x\to0}y'(x)=\frac{y_0^2+4y_0+4}{(2+y_0)^2}=1$$

So no matter what value of $y_0$ I have, the limit will always be 1. Where did I misunderstand or did wrong? Any help will be great, stuck about 2 days...

$\endgroup$
2
$\begingroup$

Observe that for $y_0=-2$ the solution $y$ of the IVP has the property that $y'$ is constant:

$$y'(x)=-2.$$

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ @Lutz: thanks for your comment. I edited my solution. $\endgroup$ – Fred Sep 29 at 8:23
2
$\begingroup$

This is, among other things, a Riccati equation. Set thus $y=-3x^2\frac{u'}{u}$ to find $$ 0=y'+\frac{2x^2-4xy-y^2}{3x^2} =\left[-3x^2\frac{u''}{u}+3x^2\frac{u'^2}{u^2}-6x\frac{u'}{u}\right] +\left[\frac23+4x\frac{u'}{u}-3x^2\frac{u'^2}{u^2}\right] \\~\\ 0=3x^2u''+2xu'-\frac23u $$ This now is an Euler-Cauchy DE with characteristic polynomial $$ 0=3m(m-1)+2m-\tfrac23=\tfrac13((3m-\tfrac12)^2-2-\tfrac14)=\tfrac13(3m-2)(3m+1) $$ So \begin{align} u&=Ax^{-1/3}+Bx^{2/3},~~~|A|+|B|\ne 0 \\~\\ \implies y(x)&=-3x^2\frac{-\frac13Ax^{-4/2}+\frac23Bx^{-1/3}}{Ax^{-1/3}+Bx^{2/3}} \\ &=x\frac{A-2Bx}{A+Bx}\\&=x-\frac{3Bx^2}{A+Bx} \\ y'(x)&=1-\frac{6ABx+3B^2x^2}{(A+Bx)^2} \end{align} For $A\ne 0$ the solution has slope 1 in $x=0$, only for $A=0$ one gets a deviating result with $y(x)=-2x$, $y'(0)=-2$. Then $y_0=y(1)=-2$.


You excluded this case from consideration in the limit $\lim_{x\to 0}y'(x)$, but did not treat this case separately. The quotient law in this limit can only be applied for $y_0+2\ne 0$.

| cite | improve this answer | |
$\endgroup$
  • 1
    $\begingroup$ This DE could as well be solved as a homogeneous DE (this is probably what is implied by your "Among other things"). For the OP: mathworld.wolfram.com/… $\endgroup$ – Jean Marie Sep 29 at 6:46
  • 1
    $\begingroup$ Yes, I guessed that this was the way OP got to his solution, as the formulation of the DE is very suggestive in that direction. Guessing $y(x)=x$ as a solution and transforming via the Bernoulli equation for $u(x)=y(x)-x$ seems less likely. $\endgroup$ – Lutz Lehmann Sep 29 at 6:55
  • $\begingroup$ Thank you very much for your time. $\endgroup$ – Will Sep 29 at 7:50

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.